Análise comparativa de planejamento de obras: método PERT/CPM x software MS Project para uma obra de 663m² na cidade de Campo Mourão - PR - Ravagnani, Matheus Silva (2017)
The growing concern about the economy in constructive ventures has made the professionals of the branch become more and more accurate, especially regarding the costs inherent to the construction industry. It is necessary to carry through a planning as a tool for the elaboration of a plan with the purpose of specifying the end of the activities, according to the necessity and priority of execution. In addition to detecting unfavorable actions, enable agility in decisions and improve the allocation of resources during the execution of the work. This course conclusion paper had the objective of applying the planning method called PERT / CPM in a building of 663m² in the city of Campo Mourão – Paraná and analyze comparatively in relation to the original planning, performed by the professional responsible for the building through the MS Project planning software. Therefore, several bibliographic references were consulted so that both the application and the comparison were effective. From the data obtained, it was possible to observe the favorable and unfavorable points of both planning methods, providing characteristics and pointing out the divergences. Moreover, this paper emphasizes the importance of planning in any constructive enterprise, irrespective of the method to be used.